PENELUSURAN SEJARAH PENDIKOTOMIAN ILMU PENGETAHUAN (UMUM DAN AGAMA) DI INDONESIA - Mohammad Kamaludin (Universitas Wijaya Kusuma Surabaya, 2021)
General science and religion are two areas of knowledge that have always been debated. Until there are assumptions that confirm each other. Actually what is going on in the world of education so there is a dichotomy of science like this. Historical searches of both may be able to find adequate answers. This research reveals the history of the separation of science (General and Religion) through fragments made by humans and especially colonial powers who deliberately divided the position of each science for the convenience and necessity of early detection of chaos. From history can be seen how religion is the upstream of all forms of teaching and education processes that existed in Indonesia before the arrival of modern sciences as it is today. Teachers, kiai, ustad, and teachers in certain places enlighten their communities using their skilled hands through religious studies. The basic religions contained in moral knowledge, natural knowledge, counting, philosophy, and mystical science are conveyed very clearly and unequivocally.Keywords : Dichotomy, General Knowledge, Religious Knowledge